Problems Of Reducing Electrical Energy Losses In Power Transmission Networks And Their Techno-Economic Solutions - Umid, Baynazov; Sardor , Nuriddinov; Dilshoda, Yusupova; Azamat, Madiyorov; Zoir, Islomov; Sherzod , Abdujaborov (Academia Open, 2026)
General Background: Electrical energy losses in transmission and distribution networks challenge economic efficiency, energy security, and environmental sustainability. Specific Background: Rising demand and renewable energy integration require more efficient network operations to minimize technical and commercial losses. Knowledge Gap: Comprehensive studies integrating power loss analysis, reactive power compensation, transformer optimization, load balancing, and intelligent control remain limited. Aims: This study analyzes modern engineering solutions for reducing energy losses and evaluates their techno-economic significance. Results: Upgrading transmission voltage, modernizing conductors, applying reactive power compensation, optimizing transformers, and balancing loads effectively reduce technical losses. Additionally, Smart Grid technologies (AMCS, SCADA, and intelligent sensors) enable real-time power flow optimization. Combining these measures can reduce total network losses by 25–30% while enhancing reliability. Novelty: This study integrates conventional engineering strategies with Smart Grid technologies into a unified techno-economic framework. Implications: The findings provide practical guidance for developing efficient, intelligent, and sustainable power networks that support renewable integration and improve energy utilization. Keywords: Electrical Energy Losses, Power Transmission Networks, Reactive Power Compensation, Smart Grid, Energy Efficiency Key Findings Highlights Higher transmission voltage levels reduce resistive losses in electrical networks. Compensation technologies improve power factor and optimize network operation. Intelligent monitoring systems support real-time control and loss minimization.